The Development of Discipline Character in Taruna Nusantara Senior High School (SMA Taruna Nusantara) (Jurnal Bimbingan Konseling, 2018)
The study of the development of discipline character took place in Taruna Nusantara Senior High School (SMA Taruna Nusantara). It was aimed at knowing what, how and why the discipline character development was conducted in SMA Taruna Nusantara. Moreover, the method used was qualitative by utilizing interview, observation and document analysis as the research instruments. Once the data collected by the instruments and furtherly analyzed, it was found that the character development conducted in SMA Taruna Nusantara covered tiered stages. The first stage was instillation. In this stage, the values of courtesy were instilled in students to become their habit. The values were realized in the way the students formed a line and gave respect to elder by raising hand. The second stage was growth stage. It was realized in any guidance given to students during their activities. The third stage was development stage. In this stage, students were given tasks such as tasks given to students' council (OSIS), class representatives, school cooperative, the committees of national days commemoration. The last stage was consolidation. This stage dealt with the responsibility of students to do any activities which were directly associated with society life. Lastly, such behavior habituation processes in social engineering are done continuously and consistently by all citizens of SMA Taruna Nusantara.